Sejarah dan Eksistensi Ekonomi Islam pada Era Global di Asia Tenggara - Putra, Popi Adiyes; Nurnasrina, Nurnasrina; Aisyah, Siti; Syukri, Mahyudin (MUI Kota Pekanbaru, 2023)
Sharia Economics of Southeast Asian countries has been existing, with a close relationship with their society, since the early arrival of Islam and its spreading in this archipelago through the period of the Islamic Kingdoms up till today. The unity of this Islamic economy with its society because the society has made their identity as Islam so that their habits, customs, economic system, and Worldview are identical to Islam. However, the implementation of the Islamic economic system and its financial activities were interrupted by the existing of colonialism. After their independence from colonization, the country such as Malaysia, Indonesia, and Brunei Darussalam initiated to raise awareness and conducted studies on the Islamic economic system. Even the government has a commitment to achieve the World's prominent center of Islamic economy. This year's report by The State of global Islamic economists reveal that ASEAN countries have succeeded in positioning their countries as a largest of sharia financial center in the world.